Counting cell in bee comb using computerized 2-dimensional shape-detection / Liew Lee Hung … [et al.] - Liew, Lee Hung; Lee, Beng Yong; Chan, Margaret Kit Yok (2019)
In the apiary industry, bee colony has to be at optimum health in order to produce most favourable amount of honey or to act as pollination agents for crop plantations. Current methods in the evaluation of bee colony health through trained personnel visual judgement and estimation and manual counting using wire grid as guidance are time consuming and the accuracy is individual dependant. This research explored the use of image processing methods to improve the existing methods. In the field of image processing, Hough transform is a common techniques used for the detection of lines and circles